2002
DOI: 10.1038/416345a
|View full text |Cite
|
Sign up to set email alerts
|

TNF-RII and c-IAP1 mediate ubiquitination and degradation of TRAF2

Abstract: Tumour necrosis factor-alpha (TNF-alpha) is a proinflammatory mediator that exerts its biological functions by binding two TNF receptors (TNF-RI and TNF-RII), which initiate biological responses by interacting with adaptor and signalling proteins. Among the signalling components that associate with TNF receptors are members of the TNF-R-associated factor (TRAF) family. TRAF2 is required for TNF-alpha-mediated activation of c-Jun N-terminal kinase (JNK), contributes to activation of NF-kappaB, and mediates anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
382
1
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 427 publications
(401 citation statements)
references
References 30 publications
17
382
1
1
Order By: Relevance
“…Whether TRAF2 negatively regulates signaling beyond competing with other signaling proteins for GITR binding is unclear. Intriguingly, TRAF2 has been shown recently to function as an E3 ubiquitin ligase and to undergo ubiquitination itself (42,54,55). Future studies will test whether ubiquitination of TRAF2 or other proteins plays a role in the novel regulatory role of TRAF2 in GITR-induced NF-B activation.…”
Section: Discussionmentioning
confidence: 99%
“…Whether TRAF2 negatively regulates signaling beyond competing with other signaling proteins for GITR binding is unclear. Intriguingly, TRAF2 has been shown recently to function as an E3 ubiquitin ligase and to undergo ubiquitination itself (42,54,55). Future studies will test whether ubiquitination of TRAF2 or other proteins plays a role in the novel regulatory role of TRAF2 in GITR-induced NF-B activation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the binding of TNF to TNFR2 induces ubiquitination of TRAF2 by c-IAP1 and subsequent proteasomal degradation of TRAF2 [51]. Thus, TNFR2 skews the signal of TNFR1 toward death by degradation of TRAF2.…”
Section: Discussionmentioning
confidence: 99%
“…We then determined if the effect of Gα o on the ubiquitination of RGS20 was specific by comparing the result of Gα o -Q/L expression on RGS20 to a well known ubiquitinated protein, Traf2 [15]. Under conditions where Gα o -Q/L stimulated the ubiquitination of RGS20 (Fig.…”
Section: Resultsmentioning
confidence: 99%